Numerical simulation and site measurements of ventilation efficiency for different types of air-conditioned rooms through window-opening natural ventilation. Issue 3 (November 2020) - Liu, Xinyu; Wang, Hanqing; Xie, Dong; Zhao, Jinping; Sang, Lixin; Wu, Xiao; Xia, Yuting; He, Zongwu
Abstract: To study the air exchange efficiency of rooms while air conditioning equipment are running and window is open, this paper used the experiments of tracer gas CO2 to measure its concentration variations indoor after opening window. At the same time, the corresponding cases were simulated numerically with computational fluid dynamic (CFD). The experimental results showed that after opening window, the combined action of wind pressure and pressure due to the differences of the air density can cause obvious air exchange between the indoor and the outdoor. Indoor CO2 concentration was continuously reduced as proceeding of the air infiltration and there is an optimized width of window opening which resulted in a fastest decay rate of CO2 concentration. Furthermore, results of simulation and experiment indicated that larger temperature difference between the indoor and outdoor lead to faster indoor CO2 exhausted rates. Air exchange rate of air-conditioned rooms is affected by the types, opening degrees and the relative locations of the window as well. Natural ventilation by reasonable window opening can enhance the air quality if the outside air is not polluted. It should be noticed that optimized width and relative location of the window opening exist if economy is to be considered.